2013
DOI: 10.1055/s-0033-1358453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Randomised Controlled Vitamin D Trial on Insulin Resistance and Glucose Metabolism in Patients with Type 2 Diabetes Mellitus

Abstract: endocrine regulator [ 5 ] . The active form of VD, 1α,25(OH) 2 D or calcitriol, is synthesised from precursor cholesterol by metabolic steps in skin, liver, and kidney. The primary metabolite, 25OHD, is the most abundant form of VD in blood and therefore established for measuring VD status. Various studies have shown an association of VD status and T2D [ 6 ] . Low 25OHD is found more often in patients with T2D [ 7 , 8 ] and correlates with a higher risk for T2D [ 6 , 9 , 10 ] . Furthermore, the 25OHD serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 12 publications
3
43
0
2
Order By: Relevance
“…The majority of trials in subjects with type 2 diabetes have also not proven an effect of vitamin D supplementation on glucose metabolism (33)(34)(35). Of special interest is a recently published study in subjects with vitamin D deficiency (mean baseline serum 25(OH)D concentration 29.7 nmol/L) (36). A few trials in subjects with Iranian ethnicity and type 2 diabetes have suggested, on the other hand, a positive effect of vitamin D supplementation on glycemic outcomes; whether this is due to ethnicity or sociocultural differences remains unknown (37).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of trials in subjects with type 2 diabetes have also not proven an effect of vitamin D supplementation on glucose metabolism (33)(34)(35). Of special interest is a recently published study in subjects with vitamin D deficiency (mean baseline serum 25(OH)D concentration 29.7 nmol/L) (36). A few trials in subjects with Iranian ethnicity and type 2 diabetes have suggested, on the other hand, a positive effect of vitamin D supplementation on glycemic outcomes; whether this is due to ethnicity or sociocultural differences remains unknown (37).…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics and main outcomes of the included studies are given in Table 1. All studies had a randomized controlled trial design, of which 18 studies used a placebo for control (12,19,20,22,23,24,25,27,29,30,31,32,33,34,35,36,37,38), three studies compared vitamin D fortified yoghurt versus plain yoghurt (21,28,39), one study used oral calcium supplementation for control (26), and one study used vitamin C supplementation for control (40). Apart from two studies, which solely included post-menopausal women (21,33), all studies included both men and women.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…While, there was a significant increase of 7.8% in fasting serum insulin and 10% in HOMA-IR in placebo group (p=0.032). 31 On the contrary, Witham etal did not observe any significant change in serum insulin levels and HOMA-IR with vitamin D supplementation. 32 This discrepancy might be because of different dosage and formulation of vitamin D used and small sample size of the study.…”
Section: Discussionmentioning
confidence: 92%